Relationship between the Divine Law and Policy in The ethics of religious propagation in the contemporary world; the values and conflicts, and the moral necessities in religious propagation from the viewpoint of Ayatollah javadi Amuli - Hasan Busaliki (حکمت اسرا, 2012)
The main subject of this study is the moral values and principles in religious propagation. Carried out through library research, this study aims at answering the research questions from the works of Ayatollah Javadi Amuli. The main research questions are investigated under two rubrics: first, with regard to the objective and contemporary concerns in religious propagation, which moral values must be emphasized? Second, what are the ways for overcoming the moral contradictions  in religious propagation? Considering the first subject, principles like “trying to transmit the message of religion, not guiding people ”,”honesty in communication of the message”,” the compatibility of words and deeds” and, “avoiding self-centrism in invitation“ have been underlined. In response to the second subject, ethics of propagation has been studied as an indigenous branch of applied ethics. Efforts have been made to present some of the conflicts in the area of propagation, and to devise solutions for such contradictions on the basis of the viewpoints of ayatollah Javadi Amuli. Under this rubric, issues like “religious propagation on a global scale”, “rationality or sentiments”,” spreading rationalism or the spirit of devotion”  have been taken into consideration.